Or, The Modern God: Biblical Allusions in Mary Shelley’s Frankenstein - Robert S. Kawashima (Religions, 2022)
Mary Shelley’s Frankenstein is largely organized around its explicit reference to Milton’s retelling of Genesis 2–3, Paradise Lost. Unfortunately, this reference to Milton has discouraged scholars from going back to the Old Testament itself. In fact, the novel contains three crucial biblical allusions. Most obvious, of course, are the allusions to creation (Genesis 1–3), which contain details not found in Milton’s epic. The biblically literate reader will be able to discern two more crucial biblical allusions: one to Exodus 32–33 and the other to the Book of Job. In both of these texts, we find a man—Moses and Job, respectively—seeking an audience with his creator, such as that Adam and Eve enjoyed in the garden.